1, 3-Dipolar cycloaddition reactions of acyl phosphonates with nitrile oxides: synthesis of phosphonate-containing dioxazole derivatives. (28th November 2020) - Polat-Cakir, Sidika
Abstract: New phosphonate-containing five-membered heterocyclic dioxazole derivatives are synthesized via 1, 3-dipolar cycloaddition reactions of nitrile oxides used as dipole with acyl phosphonates under basic conditions. Herein, acyl phosphonates take part in the cyclization process as a dipolarophile to afford the related dioxazole compounds in moderate-to-good yields (49–84%). Substituted aryl nitrile oxides and aroyl phosphonates were employed in the 1, 3-dipolar cycloaddition reactions where triethylamine was the effective tertiary base. Alkyl version of acyl phosphonate also afforded the expected cycloadduct, that is, dimethyl 5-isopropyl-3-phenyl-1, 4, 2-dioxazol-5-yl-5-phosphonate. Diethyl/dimethyl 3, 5-aryl-1, 4, 2-dioxazol-5-yl-5-phosphonate derivatives are fully characterized by using 1 H NMR, 13 C NMR, 31 P-NMR, and FT along with high-resolution mass spectroscopy. Graphical Abstract: